Adaptive Leadership 5.0: Integration of AI and Emotional Intelligence (EQ) in the Organizational Transformation Process of Bank Muamalat West Sumatra in the Vuca Era - Sarianti, Kiki; Rosalina, Desi; Andrefson, Edo (SAFE-Network, 2025)
This study explores the role of Adaptive Leadership 5.0, an integrative leadership model combining Artificial Intelligence (AI) and Emotional Intelligence (EQ), in facilitating organizational transformation within Bank Muamalat West Sumatra in response to VUCA (Volatility, Uncertainty, Complexity, Ambiguity) challenges. Employing a quantitative method using Structural Equation Modeling Partial Least Squares (SEM-PLS), data were gathered from 85 respondents through online surveys, complemented by qualitative insights from expert interviews. The findings reveal that while AI and EQ do not have a significant direct impact on organizational transformation, both significantly influence VUCA responsiveness. Specifically, adaptive leadership significantly enhances transformation outcomes and reduces VUCA effects. AI has a significant positive impact on VUCA but not directly on transformation, whereas EQ strongly influences VUCA but lacks direct influence on transformation outcomes. These results suggest that technological and emotional capacities function more effectively as mediating mechanisms rather than primary drivers of change. The study contributes theoretically by advancing the concept of Adaptive Leadership 5.0 within the context of Islamic banking and highlights practical implications for leadership development programs that emphasize the ethical integration of digital innovation and emotional intelligence.